2018
DOI: 10.1111/1742-6723.13094
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors that influence adult presentation to an emergency department in regional Queensland: A linked, cross‐sectional, patient perspective study

Abstract: Despite being connected to a general practice, people focussed their health-seeking behaviour on the ED in the immediate period prior to presentation. Patients reported a limited awareness of alternative health services and opportunities exist to potentially reduce ED attendance, particularly for young and middle-aged adults with chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Analyses of this patient survey have been reported elsewhere. 16 In the study period, 3229 individual adults (aged !18 years) attended the ED including international, inter-state and intrastate visitors. For this present study, only adults who agreed to participate in the survey and self-identified as residing locally were included in the data linkage (n ¼ 1014).…”
Section: Study Population and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of this patient survey have been reported elsewhere. 16 In the study period, 3229 individual adults (aged !18 years) attended the ED including international, inter-state and intrastate visitors. For this present study, only adults who agreed to participate in the survey and self-identified as residing locally were included in the data linkage (n ¼ 1014).…”
Section: Study Population and Settingmentioning
confidence: 99%
“…Our study was limited in several ways; the study sample was sourced from the ED waiting room; when compared with the wider ED cohort, earlier research indicated that this sample was typical for gender but slightly older in age; 16 study respondents were more likely to have arrived by ambulance and to be discharged home; 16 the patient survey was a piloted, but non-validated tool that had previously been used by health services; 16 and our study involved one hospital and further investigation is indicated to inform on other sites.…”
Section: Limitationsmentioning
confidence: 99%
“…In a study published elsewhere, we explored factors that influenced the presentation of adults to the Cairns Hospital ED. Ethics approval for the study was obtained from the Far North Queensland Human Research Ethics Committee (reference, HREC/16/QCH/81‐1068).…”
mentioning
confidence: 99%
“…1 Inaccurate representation of Indigenous status in datasets has been previously identified, and government agencies have been directed to improve data quality, and particularly to reduce the underreporting of Indigenous status. 2,3 In a study published elsewhere, 4 we explored factors that influenced the presentation of adults to the Cairns Hospital ED. Ethics approval for the study was obtained from the Far North Queensland Human Research Ethics Committee (reference, HREC/16/ QCH/81-1068).…”
mentioning
confidence: 99%
“…Six studies reported on the proportions of patients seeking alternative care or advice before visiting an ED [12,18,19,20,21,22]. While more information could be inferred from some of the referral data, we chose to present data from studies that speci cally reported on advice seeking or patient pathways to the ED.…”
Section: Resultsmentioning
confidence: 99%